Antimicrobial susceptibility of uropathogens and prescribing patterns in hospital- and community-acquired urinary tract infections in a tertiary care hospital - Achukutty Tomy, Aravind Hareendran, Emil David, Ravina Ravi, Lakshmi Ramachandran, Appu Thomas (Journal of Applied Pharmaceutical Science, 2020)
Periodic surveillances on the prevalence and antimicrobial susceptibility of uropathogens are necessary as they vary with time and geography. This prospective study for 8 months included 331 and 335 patients with hospital-acquired and community-acquired urinary tract infections (HA-UTI and CA-UTI), respectively. The prevalence of Gram-negative bacilli was higher in both groups, with Escherichia coli being the most prevalent uropathogen in both groups. An alarming number of isolates with multiple drug resistance was observed in HA-UTI and CA-UTI (47% and 46.2%, respectively). The mean multiple antibiotic resistance index in both groups was >0.2. Prescribing patterns and percentage antimicrobial susceptibility antibiograms revealed high resistance to commonly prescribed antimicrobials like ß-lactams and fluoroquinolones. Retrospective data of the preceding 2 years revealed a statistically significant reduction in antimicrobial sensitivity of E. coli and Klebsiella isolates to several antibiotics. Antibiotic resistance is a major threat to patient safety in the hospital and the community. Strengthening of antimicrobial stewardship strategies like continued antimicrobial susceptibility surveillance, framing empirical antimicrobial policies, and promoting rational prescription of antimicrobials is the need of the hour.
Keywords: Urinary tract infections, antimicrobial susceptibility, multiple drug resistance, multiple antibiotic resistance index, antimicrobial stewardship.